Encyclopedia of small business - Darnay, Arsen; Magee, Monique D.; Hillstrom, Kevin 1963- (Gale virtual reference library, 2007)
This convenient and exhaustive print reference source is designed to provide entrepreneurs with how-to information that they can apply to their own business. The Encyclopedia contains detailed articles and overviews of all the key information needs of small business users, including financing; financial planning; business plan creation; market analysis; sales strategy; tax planning and more.